2013
DOI: 10.3892/mmr.2013.1817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human interleukin-10 on Treg cells, IL-10 and TGF-β in transplantation of rabbit skin

Abstract: The current study aimed to investigate the rejection and survival time of grafted skin, and the changes of Treg cells, interleukin 10 (IL-10) and transforming growth factor-β (TGF-β) in peripheral blood following skin transplantation with recombinant human interleukin-10 (rhIL-10) or cyclosporin A (CsA), as well as the role of IL-10 in immunological rejection mechanisms. A total of 36 rabbits were divided into two groups. The skin of a donor rabbit was transplanted onto the back of one receptor rabbit. Recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…IL-10 is an anti-inflammatory, anti-fibrotic immunoregulatory cytokine, which attenuates alloimmune response and displays pleiotropic effects on both innate and adaptive immunity [ 24 , 25 , 26 , 33 , 60 , 61 , 62 ]. Several experimental studies have demonstrated that IL-10 administration before transplantation facilitates tissue repair and graft survival [ 43 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-10 is an anti-inflammatory, anti-fibrotic immunoregulatory cytokine, which attenuates alloimmune response and displays pleiotropic effects on both innate and adaptive immunity [ 24 , 25 , 26 , 33 , 60 , 61 , 62 ]. Several experimental studies have demonstrated that IL-10 administration before transplantation facilitates tissue repair and graft survival [ 43 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-10-mediated immune modulation and protection have been demonstrated in preclinical and clinical studies which highlighted the key immunosuppressive, protective, and antifibrotic roles of IL-10 in delaying the progression of fibrosis after transplantation [ 25 , 31 , 43 , 87 ]. IL-10 inhibits ischemia/reperfusion injury [ 78 , 88 ], prolongs allograft survival [ 61 , 87 ], and is essential for the action of Tregs mediating tolerance in different transplant models [ 28 , 62 , 89 , 90 ]. Besides, IL-10 is required for the immunoregulatory activity of Tregs as reported in the mouse model of skin transplantation, which demonstrated that blockade of IL-10 pathways abrogated immunoregulation mediated by CD25 + T cells [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IL-10 can assist the differentiation of infantile T cells into Treg cells, while Treg cells can secrete IL-10. Positive feedback regulation between Treg cells and IL-10 may promote immune tolerance ( 60 62 ). Therefore, AFP can cause upregulation of Fas and FasL expression in Treg cells and promote the secretion of IL-10 by PD-1/PD-L signaling, leading to the inhibition of the proliferation of CD8 + T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 has been reported to modulate regulatory T cells (Tregs) and conserve FOXP3 expression and associated suppressive function [3,4]. In addition, IL-10 influences wound healing, tissue repair, angiogenesis, and antifibrotic properties as reported in several preclinical studies including transplantation [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%